A just recovery from the COVID-19 pandemic for people with disabilities: Descriptive analysis of Canadian survey data - Pahwa, Manisha; Dhaliwal, Hazel; Lee, Jocelyn; Mahamad, Syed; Murdoch, Em (Prepared by the McMaster Research Shop for the Disability Justice Network of Ontario, 2022)
Emerging research shows that people with disabilities have experienced a worsening of economic and health status, housing conditions, social support, and personal safety during the COVID-19 pandemic. Policy responses to COVID-19 have neglected the needs of people with disabilities, prompting community organizations to advocate for a just recovery that centres disabled people. In 2021 the Disability Justice Network of Ontario (DJNO) conducted an online, national survey asking people with disabilities about their experiences during the COVID-19 pandemic and what their needs are for a just recovery. The survey collected quantitative and qualitative data in multiple domains, including respondent demographic information, just recovery/quality of life, education and labour force, social services and the justice system, housing, and health care. This report presents a descriptive analysis of DJNO’s survey results for Ontario respondents. The results of this survey revealed an urgent and large need for economic, social, housing, and health support for people with disabilities.
Keywords: Hamilton, community-engaged research, disability justice, just recovery, COVID-19, descriptive analysis